SCADA PROCESS VARIABLES MONITIORING INTEGRATED IN RF NETWORK (Balkan Journal of Applied Mathematics and Informatics, 2024)
In this paper results fromt the developed design and practical implementation of the SCADA system are represented. The solution collects, measures, stores and displays the process data in an industrial plant. The SCADA system includes IoT RF communication between MASTER and SLAVE stations. Some of the hardware sensors and components are installed in SLAVE station and some in MASTER station. The communication between the SLAVE and MASTER stations is ensured by a microcomputer and RF modules.